Membangun Mindset dan Motivasi Siswa SMA Plus Nw Islam Pohgading untuk Melanjutkan Studi ke Perguruan Tinggi - Dani Anggara; Nur Mujahadah; Lalu Amrullah; Usman Usman; Imam Hidayatullah (Jurnal Pengabdian Masyarakat Sains dan Teknologi, 2024)
Limited information on higher education for people living in rural areas results in a lack of information about teenagers' interest in continuing their studies to a higher level. This problem causes higher education to experience a decrease in the number of new students every year. The village's advanced economic level does not support the education of its people, so that the average population still has secondary level education. The aim of this community service activity is to provide motivation and education about higher education. The techniques used in this activity are survey, face-to-face and discussion techniques. From educational sharing and discussion activities, it was found that high motivation for higher education was not supported by an attitude of agreeing to continue higher education. Sharing education about higher education at the end provides enlightenment that higher education can be achieved by all levels of society by choosing universities that provide low funding schemes and scholarship schemes.